CONFERENCE PROCEEDINGS : NATIONAL CONFERENCE ON DENTAL EDUCATION HELD ON 14-15TH NOVEMBER 2014, ORGANIZED BY LIAQUAT UNIVERSITY OF MEDICAL & HEALTH SCIENCES, JAMSHORO - Katpar, Shahjahan; Kumar, Naresh; Ahmad, Amina; Siddiqui, Faisal Ghani (Pakistan Armed Forces Medical Journal, 2016)
Conference Abstract To present Pakistan’s national conference on dental education proceedings, held on 14th-15th November 2014 organized by Institute of Dentistry, Liaquat University of Medical & Health Sciences (LUMHS), Jamshoro.